The Medieval Welsh Englynion y Beddau The 'Stanzas of the Graves', or 'Graves of the Warriors of the Island of Britain', Attributed to Taliesin. - Sims-Williams, Patrick (Studies in Celtic History Series., 2023)
Edition and translation of this important genre of Old Welsh poetry.